2016
DOI: 10.17816/uroved6216-22
|View full text |Cite
|
Sign up to set email alerts
|

Use of Kanefron in treatment of acute uncomplicated cystitis in women

Abstract: Целью работы явилась оценка эффективности и безопасности применения канеф-рона при неосложненном цистите у женщин в реальной клинической практике. Пациенты и методы. В нашей работе приняли участие 22 женщины с диагнозом «острый неосложненный цистит». Средний возраст составил 29,0 ± 1,8 года (от 19 до 51 года). Критериями эффективности были изменение симптоматики и лабораторных показателей по данным общего анализа и посева мочи при монотерапии канефроном. Результаты. При лечении канефроном наблюдали выраженное … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…The results presented are not surprising, since Canephron ® is a well-studied, approved medicinal product. Amdii et al previously concluded that treatment with Canephron ® N allows the use of antibiotics to be reduced in women with uUTIs [25]. Wagenlehner et al performed a Phase III, non-inferiority trial including 659 women and found a non-inferior difference between patients treated with Canephron ® N and those receiving antibiotics, with regard to the proportion of women requiring additional antibiotics [21].…”
Section: Discussionmentioning
confidence: 99%
“…The results presented are not surprising, since Canephron ® is a well-studied, approved medicinal product. Amdii et al previously concluded that treatment with Canephron ® N allows the use of antibiotics to be reduced in women with uUTIs [25]. Wagenlehner et al performed a Phase III, non-inferiority trial including 659 women and found a non-inferior difference between patients treated with Canephron ® N and those receiving antibiotics, with regard to the proportion of women requiring additional antibiotics [21].…”
Section: Discussionmentioning
confidence: 99%
“…The second group of animals was left untreated. The third group was treated for acute cystitis by daily oral administration of the drug «Canefron ® N», which has proven effectiveness in the treatment of infectious diseases of the urinary tract in the form of drops at the rate of 2 drops per day [23]. In the fourth group of animals, treatment was performed with condensed juice of Vaccinium oxycoccos fruit, administered to rats orally at the rate of 0.01 g per day.…”
Section: Methodsmentioning
confidence: 99%
“…of 60 mg•kg 1 body weight of animals intraperitoneally). The collected material (bladder) was fixed for 14 days in a 10 % solution of neutral formalin (pH-7.0), and then carried out to paraffin blocks according to conventional methods [23]. Sections with a thickness of 5-8 μm were obtained, followed by staining with hematoxylin and eosin.…”
Section: Methodsmentioning
confidence: 99%
“…В этой связи в нашей стране и за рубежом отмечается существенное повышение интереса к неантибактериальной профилактике рецидивирующих ИНМП [13][14][15]. В настоящее время с этой целью уже нашли применение в широкой клинической практике поведенческие методики, иммуно-и фитопрепараты, пре-и пробиотики [15][16][17].…”
Section: Introductionunclassified